Monitoring and speed control of AC motor using PWM technique - Sudhakar, Ambarapu; Kumari, Popuri Rajani; Batakala, Jeevanrao; Kumar, Munuswamy Siva; Prakash, Nelaturi Nanda; Kameswari, Yeluripati Lalitha; Rajanna, Bodapati Venkata; Bhavana, Mukku (International Journal of Applied Power Engineering (IJAPE), 2024)
This study focuses on how to monitor and regulate the speed of an AC motor using pulse width modulation (PWM) technology. PWM signals regulate motor voltage and enable continuous monitoring of voltage, current, and speed in addition to speed control. Comparing this technology to conventional techniques yields considerable advantages like enhanced power and speed control. PWM-based speed control can be implemented using circuits specifically designed for motor control or microcontrollers. It has been confirmed that PWM-based control can regulate the target motor under a variety of operating conditions and that it is reliable and efficient. To boost production and efficiency, this change management technique can be applied in a variety of industries, including robots, HVAC systems, and industrial automation. The study results show the significance of PWM technology for monitoring and controlling the speed of AC motors, providing productive and affordable solutions to a range of enterprises and sectors.